Edukasi dan Intervensi Gizi untuk Mencegah Stunting : Studi Kasus Program KKN New Zero Stunting Desa Jatiwangi - Supartono; Adelia, Putri; Savitri, Meidiana; Baskoro, Renaldi Adi; Mufidah, Anisatul; ., Khoerunnisa; Aprilia, Elsa; Hanif, Muhammad Ammar; Handayani, Anis Fadhillah Setya (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
The KKN New Zero Stunting program in Jatiwangi Village implemented a holistic approach to stunting prevention, including participatory nutrition education, empowerment of nutrition cadres, and sensitive nutrition interventions. This case study analyzes the program's implementation using qualitative methods through in-depth interviews, participatory observation, and focus group discussions. Results show positive changes in community knowledge, attitudes, and nutrition practices. Socio-cultural factors such as the dominant role of parents and in-laws, perceptions of "good food" for children, and food taboos during pregnancy have significant influence. Participatory and culturally sensitive approaches proved effective in increasing community involvement. Empowering local nutrition cadres is key to the sustainability of stunting prevention programs at the village level.